2023
DOI: 10.3389/fcvm.2023.1138356
|View full text |Cite
|
Sign up to set email alerts
|

The pre-ejection period is a highly stress dependent parameter of paramount importance for pulse-wave-velocity based applications

Abstract: PurposeThe pulse-wave-velocity, is used for indirect, cuff-less, continuous blood pressure estimation. It is commonly detected by measuring the time delay between a defined point in an ECG and the arrival of the peripheral pulse wave (e.g., oxygen saturation sensor). The period between electrical stimulation of the heart (ECG) and actual blood ejection from the heart is called the pre-ejection period (PEP). This study aims at characterizing the PEP under mental and physical stress with focus on its relations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However, the use of PTT as a surrogate BP marker may be complicated by the PEP component, as PEP is strongly influenced by mechanical and electrical cardiac factors, which may negate BP correlations [ 23 ]. Additionally, PEP is highly inter-individual dependent and is strongly influenced by sympathetic tone during mental stress, which may have implications when used in a general perioperative setting [ 24 ]. Previous work by Finnegan et al found that during vasoactive administration, PTT showed greater correlations with BP than PAT [ 18 ], a finding highly relevant to the use of PTT in the perioperative setting, where the use of vasoactive medications is quite common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of PTT as a surrogate BP marker may be complicated by the PEP component, as PEP is strongly influenced by mechanical and electrical cardiac factors, which may negate BP correlations [ 23 ]. Additionally, PEP is highly inter-individual dependent and is strongly influenced by sympathetic tone during mental stress, which may have implications when used in a general perioperative setting [ 24 ]. Previous work by Finnegan et al found that during vasoactive administration, PTT showed greater correlations with BP than PAT [ 18 ], a finding highly relevant to the use of PTT in the perioperative setting, where the use of vasoactive medications is quite common.…”
Section: Discussionmentioning
confidence: 99%
“…All three signals indicate distinct characteristics of the PW. PEP is strongly influenced by sympathetic tone [ 24 ], and the use of PEP may have altered the correlation results presented here. For the purpose of this proof-of-concept study, we chose to use the R-wave of the ECG as a starting point.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of physiological models is vast: ranging from proteomics 1 to animal models 2 and extending into the realm of laboratory 3 and applied human physiology. 4 They assist in deconstructing complex biological phenomena into constituent parts.…”
Section: Bridging the Gap: The Dichotomy Between Measurement And Real...mentioning
confidence: 99%
“…This, in consequence, enables motivated and bright scientists to devise pragmatic methods of seeking answers to these unresolved mysteries. The spectrum of physiological models is vast: ranging from proteomics 1 to animal models 2 and extending into the realm of laboratory 3 and applied human physiology 4 . They assist in deconstructing complex biological phenomena into constituent parts.…”
mentioning
confidence: 99%
“…Extremes in temperature, variations in gravity, physical exertion, organ system pathologies, or psychological stressors change what our regulatory systems consider as normal 6,7 . These circumstances necessitate adaptations in our physiology, which can be temporary, lead to a new hemostatic balance, or progressively alter and possibly harm our long‐term functionality 8,9 …”
Section: Figurementioning
confidence: 99%